Description of ontogenetic changes in the morphology of Amblyseius herbicolus (Chant, 1959) and Amblyseius lentiginosus Denmark & Schicha, 1974 (Acari: Phytoseiidae) - Ma, Min; Zhang, Keshi; Fan, Qing-Hai; Zhang, Zhi-Qiang (Zootaxa, 2024)
This paper provides a comprehensive description of the morphological characteristics of the developmental stages (larva, protonymph, deutonymph, and adult) of Amblyseius herbicolus (Chant, 1959) and Amblyseius lentiginosus Denmark & Schicha, 1974. Both species used were sourced from laboratory-reared colonies fed with the dried fruit mite Carpoglyphus lactis (L.) (Acari: Carpoglyphidae).